Advances in Grid and Pervasive Computing 7th International Conference, GPC 2012, Hong Kong, China, May 11-13, 2012, Proceedings - Li, Ruixuan; Cao, Jiannong; Bourgeois, Julien (Theoretical Computer Science and General Issues, 2012)
This book constitutes the refereed proceedings of the 7th International Conference on Grid and Pervasive Computing, GPC 2012, held in Hong Kong, China, in May 2012. The 9 revised full papers and 19 short papers were carefully revised and selected from 55 submissions. They are organized in topical sections on cloud computing, grid and service computing, green computing, mobile and pervasive computing, scheduling and performance, and trust and security. Also included are 4 papers presented at the 2012 International Workshop on Mobile Cloud and Ubiquitous Computing (Mobi-Cloud 2012) held in conjunction with GPC 2012.